2010
DOI: 10.1177/104063871002200510
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Two Methods for Blood Lead Analysis in Cattle: Graphite-Furnace Atomic Absorption Spectrometry and Leadcare® II System

Abstract: Abstract. The current study compared the LeadCareH II test kit system with graphite-furnace atomic absorption spectrometry for blood lead (Pb) analysis in 56 cattle accidentally exposed to Pb in the field. Blood Pb concentrations were determined by LeadCare II within 4 hr of collection and after 72 hr of refrigeration. Blood Pb concentrations were determined by atomic absorption spectrometry, and samples that were coagulated (n 5 12) were homogenized before analysis. There was strong rank correlation (R 2 5 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 14 publications
2
8
0
Order By: Relevance
“…In fact, as far as we know, only one study has been conducted very recently with respect to birds (Herring et al 2018). Once again, in a similar way to the previous studies using the LeadCare I and in the same manner through which the results that we obtained in the case of raptors using the LCII, Bischoff et al (2010) found that there was a strong correlation between the values measured by both techniques in cattle samples (Spearman's r ¼ 0.93, n ¼ 56), but they also reported that the LCII has tendency to imprecisely quantify the actual BLLs. Once again, in a similar way to the previous studies using the LeadCare I and in the same manner through which the results that we obtained in the case of raptors using the LCII, Bischoff et al (2010) found that there was a strong correlation between the values measured by both techniques in cattle samples (Spearman's r ¼ 0.93, n ¼ 56), but they also reported that the LCII has tendency to imprecisely quantify the actual BLLs.…”
Section: Discussionsupporting
confidence: 58%
“…In fact, as far as we know, only one study has been conducted very recently with respect to birds (Herring et al 2018). Once again, in a similar way to the previous studies using the LeadCare I and in the same manner through which the results that we obtained in the case of raptors using the LCII, Bischoff et al (2010) found that there was a strong correlation between the values measured by both techniques in cattle samples (Spearman's r ¼ 0.93, n ¼ 56), but they also reported that the LCII has tendency to imprecisely quantify the actual BLLs. Once again, in a similar way to the previous studies using the LeadCare I and in the same manner through which the results that we obtained in the case of raptors using the LCII, Bischoff et al (2010) found that there was a strong correlation between the values measured by both techniques in cattle samples (Spearman's r ¼ 0.93, n ¼ 56), but they also reported that the LCII has tendency to imprecisely quantify the actual BLLs.…”
Section: Discussionsupporting
confidence: 58%
“…The results from this study showed that effective stabilization in goats. Graphite-furnace atomic absorption spectroscopy used to determine the concentration of heavy metals and also blood selenium concentrations of goats and cattle [ 208 , 209 ], lead and cadmium concentrations in goat, cow, sheep, and buffalo milks [ 210 ].…”
Section: Types Of Various Nanomaterials Used In Veterinary Medicinmentioning
confidence: 99%
“…The LeadCare® analyzers from Magellan Diagnostics Inc. (North Billerica, MA, USA) apply ASV technology. These analyzers are validated for humans (26), some avian species (27, 28) and in cattle (29) by comparison to the GFAAS and/or ICP-MS. Furthermore, ASV has been used in studies investigating lead exposure in grizzly bears ( Ursus arctos ), black bears ( U. americanus ), gray wolves ( Canis lupus ) and cougars ( Puma concolor ) (30), and multiple avian species (31, 32).…”
Section: Introductionmentioning
confidence: 99%
“…In studies comparing the LeadCare® systems with GFAAS or ICP-MS, the ASV analyzers had a negative bias (i.e., underestimation) when measuring the BLL of avian wildlife (27, 33) and cattle (29). Validation for each species has been proposed to verify the conversion rate when using the LeadCare® to monitor exposure (23).…”
Section: Introductionmentioning
confidence: 99%